Bimodality treatment of patients with pelvic adenoid cystic carcinoma with photon intensity-modulated radiotherapy plus carbon ion boost: a case series - Bernhardt, Denise; Sterzing, Florian; Adeberg, Sebastian; Herfarth, Klaus; Katayama, Sonja; Hörner-Rieber, Juliane; König, Laila; Debus, Jürgen; Rieken, Stefan (Cancer management and research, 2018)
Bimodality treatment of patients with pelvic adenoid cystic carcinoma with photon intensity-modulated radiotherapy plus carbon ion boost: a case series Denise Bernhardt,1–3 Florian Sterzing,1–4,5 Sebastian Adeberg,1–4 Klaus Herfarth,1–3 Sonja Katayama,1,3 Robert Foerster,1,3,6 Juliane Hoerner-Rieber,1,3 Laila König,1,3 Juergen Debus,1–4 Stefan Rieken,1,3 1Department of Radiation Oncology, University Hospital of Heidelberg, Heidelberg, Germany; 2Heidelberg Ion-Beam Therapy Center (HIT), Heidelberg, Germany; 3Heidelberg Institute of Radiation Oncology (HIRO), Heidelberg, Germany; 4Clinical Cooperation Unit Radiation Oncology, German Cancer Research Center (DKFZ), Heidelberg, Germany; 5Department of Radiation Oncology, Klinikum Kempten, Kempten, Germany; 6Department of Radiation Oncology, University Hospital of Zürich, Zürich, Switzerland Background: Treatment of patients with pelvic adenoid cystic carcinoma (ACC) remains a challenge owing to the rarity of the disease, the lack of data, and the relative radioresistance of these tumors.Case reports: This case series presents the results of three patients with recurrent or inoperable pelvic ACC treated with intensity-modulated radiotherapy (IMRT) plus carbon ion (C12) boost. Patients received C12 therapy at a dose of 3 Gray equivalents (GyE) (relative biological effectiveness [RBE]) per fraction up to 24 GyE RBE, followed by 50 GyE of photon IMRT in 25 fractions.Conclusion: IMRT plus C12 ion boost as a definitive or adjuvant treatment for pelvic ACCs seems to be a promising therapeutic option. No unexpected toxicity was detected and the observed toxicity remained consistently low. The initial treatment response is promising and similar to that experienced for head and neck ACCs. Keywords: ACC of Bartholin’s gland, adenoid cystic carcinoma, ACC of the prostate, ion therapy, IMRT, tomotherapy, particle irradiation, carbon ion